The Surprisingly Modest Relationship Between SES and Educational Achievement. Issue 2 (3rd April 2017) - Harwell, Michael; Maeda, Yukiko; Bishop, Kyoungwon; Xie, Aolin
ABSTRACT: Measures of socioeconomic status (SES) are routinely used in analyses of achievement data to increase statistical power, statistically control for the effects of SES, and enhance causality arguments under the premise that the SES-achievement relationship is moderate to strong. Empirical evidence characterizing the strength of the SES-achievement relationship and its moderators suggests that this relationship is surprisingly modest, with an average SES-achievement correlation of .22, although it appears to have strengthened in the past 3 decades. The modest SES-achievement relationship has important implications for using SES measures in educational data analyses. We provide evidence of this relationship and of the need to use theoretical models to guide the construction and selection of SES measures in analyses of achievement data.